Aid, growth, and development: Have we come full circle? - Channing Arndt; Sam Jones; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
The micro-macro paradox has been revived. Despite broadly positive evaluations at the micro and meso-levels, recent literature doubts the ability of foreign aid to foster economic growth and development. This paper assesses the aid-growth literature and, taking inspiration from the program evaluation literature, we re-examine key hypotheses. In our findings, aid has a positive and statistically significant causal effect on growth over the long run, with confidence intervals conforming to levels suggested by growth theory. Aid remains a key tool for enhancing the development prospects of poor countries.
Keywords: O1; O4; F35; C21; 330; foreign aid; growth; aid effectiveness; causal effects